Examining the Influence of Fintech Adoption on Green Finance and Environmental Performance in Financial Institutions: Exploring the Mediating Role of Green Innovation - Thomas, Subin; Nair, Dhanya S.; A., Suchitra; Jose, Josheena; James, Jaimol; Bose, Jacob (International Journal of Economics and Financial Issues, 2025)
Technological advancements are integral in achieving the sustainability goals of a nation. In the financial sector, technology-integrated Fintech Adoption (FA) is considered a revolutionary change in financial services delivery. Substantial empirical evidences exist to establish how the Environmental Performance (EP) of the organizations is affected by Green Innovation (GI) and Green Finance (GF). In the finance sector, only limited researches were carried out to understand the relationship between Environmental Performance, Fintech Adoption, Green Innovation and Green Finance. The present study was undertaken among the financial institutions in the Bagmati province of Nepal. The empirical research findings endorse that the Adoption of Fintech significantly impact Green Innovation, Environmental Performance and Green Finance. The study also confirmed that a firm’s Environmental Performance is significantly affected by Green Finance and Green Innovation. The researchers established the mediating effect of Green Innovation in the association among the variables Adoption of Fintech, Environmental Performance and Green Finance. The study confirms that in enhancing the Environmental Performance of the financial institutions, Green Innovation, Fintech Adoption, and Green Finance play a crucial role.